ANALISIS KEMAMPUAN HIGHER ORDER THINKING SKILLS (HOTS) PADA PESERTA DIDIK KELAS 4 DALAM PEMBELAJARAN IPAS DI MI AL-FALAH - Hanani, Sofiatul; Anwar Badruttamam, Choerul; Zahrotul Mufidah, Nani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the Higher Order Thinking Skills (HOTS) of fourth-grade students in the IPAS subject at MI Al-Falah. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings revealed that the implementation of HOTS-based learning has begun, particularly through discussions, case studies, and open-ended questions, although it is not yet fully integrated across all learning stages. Assessment practices are still largely focused on lower-order cognitive skills, although teachers have started to incorporate HOTS-based questions. Students responded positively to HOTS-oriented learning activities, showing increased enthusiasm and participation, although some still require guided practice in critical thinking. This study recommends ongoing teacher training and the development of learning strategies that foster high-order thinking from an early stage.